2006
DOI: 10.1002/dvdy.20973
|View full text |Cite
|
Sign up to set email alerts
|

Latrophilin‐2 is a novel component of the epithelial‐mesenchymal transition within the atrioventricular canal of the embryonic chicken heart

Abstract: Endothelial cells in the atrioventricular canal of the heart undergo an epithelial-mesenchymal transition (EMT) to form heart valves. We surveyed an on-line database (http://www.geisha.arizona.edu/) for clones expressed during gastrulation to identify novel EMT components. One gene, latrophilin-2, was identified as expressed in the heart and appeared to be functional in EMT. This molecule was chosen for further examination. In situ localization showed it to be expressed in both the myocardium and endothelium. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…LPHN2 is an adhesion GPCR (group I) belonging to the family of latrophilins composed of three members (LPHN1-3) (for review see [140]). Expression of latrophilin 1 and 3 is mainly found in the central nervous system, whereas LPHN2 is more ubiquitous [140], [141], [142], [143]. LPHN2 shares with the two other members a large N-terminus composed of lectin, olfactomedin and hormone binding domains.…”
Section: Discussionmentioning
confidence: 99%
“…LPHN2 is an adhesion GPCR (group I) belonging to the family of latrophilins composed of three members (LPHN1-3) (for review see [140]). Expression of latrophilin 1 and 3 is mainly found in the central nervous system, whereas LPHN2 is more ubiquitous [140], [141], [142], [143]. LPHN2 shares with the two other members a large N-terminus composed of lectin, olfactomedin and hormone binding domains.…”
Section: Discussionmentioning
confidence: 99%
“…ADGRL2 (latrophilin-2) expression is required for normal epithelial-mesenchymal transition of endothelial cells in the atrioventricular canal of the heart during early chick development; however, it is unclear how ADGRL2 (latrophilin-2) controls this transition (Doyle et al, 2006). In zebrafish and mice, ADGRG6 (GPR126) signaling is required for Schwann cell differentiation, as elevation of cAMP mediated by ADGRG6 (GPR126) is necessary for the terminal differentiation of myelinating Schwann cells (Monk et al, 2009(Monk et al, , 2011Glenn and Talbot, 2013;Mogha et al, 2013).…”
Section: Physiology and Diseasementioning
confidence: 99%
“…Several Adhesion GPCRs are associated with the cardiovascular system. ADGRL2 (latrophilin-2) is required for heart valve formation, acting as a component of the epithelialmesenchymal transition in the atrioventricular canal 354 (Doyle et al, 2006). ADGRL1 (latrophilin-1) expression has been detected during rat heart development, but its function is unclear (Ferrand et al, 1999).…”
Section: Hematopoietic System and Immunitymentioning
confidence: 99%
“…Also, orphan receptor latrophilin-2 (encoded by Lphn2) was upregulated in ECsc derived from EAE mice, but in contrast to F2r and Darc, it was rather associated with a less-activated endothelial phenotype. The latrophilin family of adhesion receptors has been implicated in regulation of cell-cell and cell-matrix interactions, but data regarding specific cellular functions of LPHN2 are, except for a putative role in EMT, lacking (57,58). Our knockdown experiments in human brain EC showed that loss of LPHN2 results in increased expression of mediators implicated in leukocyte adhesion and transmigration through the endothelial barrier, such as IL-8 (59), CXCL11 (60), CXCL12 (61), or chemokine binding proteins syndecan and CD44 (37).…”
Section: Discussionmentioning
confidence: 99%